Coherent Coolant Delivery in Grinding - Lightstone, Maxwell Samuel (My University, 2021)
Coolant application is critically important in grinding, preventing workpiece damage and increasing the quality of manufactured components. However, delivery of grinding fluids is difficult to achieve, due to issues unique to grinding processes such as the air layer that surrounds the wheel. Coherent jets, which maintain their shape over a significant distance, are one of the most effective methods of coolant delivery and a significant amount of research has been devoted to developing them. Results of this work, which has largely focused on contoured nozzles, have been modest. Inspired by laminar fountains and wind tunnel design, the present work focuses on the development of a coherent, laminar jet. The developed jet possesses extreme coherence, and appears to resemble a glass rod with its stability and clarity. Investigations were carried out, comparing the coherence and cooling ability of the developed system to that of a commercially available coherent nozzle. Models for the structure of the air layer and to predict the conditions necessary for a jet to penetrate the air layer were also developed. The developed jet outperformed the commercial system both in terms of coherence and manufacturing productivity. The model was validated with experimental values, and appears to provide excellent agreement to those results. This work details the background, design, and experimentation involved in creating these innovative systems.
A Study of Coherent Jets and their Ability to Deliver Grinding Fluid
Keywords: Grinding; manufacturing; coherent jet; grinding burn; grinding fluid; lubrication; laminar jet; hydraulic flip